2022
DOI: 10.1175/waf-d-21-0080.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Usefulness of Lightning Forecasts Made with Lightning Parameterization Schemes Coupled with the WRF Model

Abstract: The evaluation and usefulness of lightning prediction for Indian subcontinent are demonstrated. Implementation of the lightning parameterizations based on storm parameters, in Weather Research and Forecasting (WRF), with different microphysics schemes are carried out. With the availability of observed lightning measurements over Maharashtra from the lightning detection network (LDN), lightning cases have been identified during pre-monsoon season of 2016–2018. Lightning parameterization based on cloud top heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Such models have gained high popularity in recent past for their accuracy and interpretability at the same time, that is, performance without being confined within the black box of ML (Johari et al ., 2009; Silva et al ., 2022). Studies (Lynn and Yair, 2010) have reported good prospects of WRF coupled models for accurate real‐time forecast of lightning activities for example, Vani et al ., 2022 proposed a model with a POD of 0.90 and FAR of 0.64. The proposed model attempts to device a single model for the first time over entire Indian region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such models have gained high popularity in recent past for their accuracy and interpretability at the same time, that is, performance without being confined within the black box of ML (Johari et al ., 2009; Silva et al ., 2022). Studies (Lynn and Yair, 2010) have reported good prospects of WRF coupled models for accurate real‐time forecast of lightning activities for example, Vani et al ., 2022 proposed a model with a POD of 0.90 and FAR of 0.64. The proposed model attempts to device a single model for the first time over entire Indian region.…”
Section: Discussionmentioning
confidence: 99%
“…Price and Rind (1992) based on cloud top height and vertically integrated ice water path reported excellent accuracy in recreating the spatial lightning pattern. Vani et al ., 2022 evaluated lightning parameterization based on cloud top height defined by reflectivity threshold for 16 pre‐monsoon storms over Maharashtra. The study reported a false alarm ratio of 0.28, 0.25, 0.29, 0.26 from WSM6, Thompson, Morrison and WDM6 parameterizations respectively.…”
Section: Introductionmentioning
confidence: 99%
“…One commonly used lightning parameterization in numerical models is based on relating the convective cloud top height and the prevailing updrafts, along with the ratio between intra‐cloud and cloud‐to‐ground lightning flashes from observations (Mohan et al., 2021; Price & Rind, 1992, 1993; Vani et al., 2022; Wong et al., 2013). In the numerical models, the ratio can assume climatology (e.g., that already incorporated over the conterminous United States by Boccippio et al., 2001).…”
Section: Introductionmentioning
confidence: 99%